Clinico-Epidemiological Study of Morphological Patterns of Allergic Contact Dermatitis due to Lac Bangles in Females of Hadoti Region - Neha Sharma; Ramesh Kumar; Devendra Yadav; Asha Nyati; Suresh Kumar Jain; Apoorva Panwar (Indian Journal of Dermatology)
Background: India is a country with diverse religious and cultural practices instigating skin diseases which may be missed due to lack of awareness. Contact dermatitis (CD) to lac is not uncommon yet an underreported entity. Objectives: To study clinical patterns of allergic CD due to lac bangles and to assess common contact allergens. Methodology: A retrospective study was conducted after approval by an ethical committee. Out of 850 patients attending the CD clinic from January 2021 to December 2022, the prevalence of CD lac bangles was 40 (4.7%). After obtaining consent, the history of sites, duration, morphology, and DLQI were recorded from patients’ medical records. Patch testing with Indian standard series (ISS) and raw lac powder mixed with control was done. Results: A total of 40 females were evaluated. The mean duration between contact and first symptom was 14.8 ± 10.43 months. Morphology was dry eczematous in 18 (45%), lichenoid in 10 (25%), oozy eczematous in 5 (12.5%), urticarial in 5 (12.5%) and vesiculobullous in 2 (5%) patients. In 14 (35%) females, lesions were disseminated. In 12 (30%) females, CD to bindi (4), lipstick (1), Sindhoor (5), rings (1), and plastic slippers (1) were associated. The mean DLQI was 19.37 ± 3.4. Patch test results were positive with ISS allergen epoxy in 9 (22.5%) patients, nickel in 6 (15%), cobalt in 6 (15%), paraphenylenediamine in 5 (12.5%), and lac in only 2 (5%) patients. Conclusion: Data observed in the present study suggests that CD to lac is a distinct clinical entity. Low positivity with lac in patch test proposes the need for standardized testing material.